2018
DOI: 10.2147/ijn.s184355
|View full text |Cite
|
Sign up to set email alerts
|

pH-sensitive PEGylation of RIPL peptide-conjugated nanostructured lipid carriers: design and in vitro evaluation

Abstract: BackgroundRIPL peptide (IPLVVPLRRRRRRRRC)-conjugated nanostructured lipid carriers (RIPL-NLCs) can facilitate selective drug delivery to hepsin (Hpn)-expressing cancer cells, but they exhibit low stability in the blood. Generally, biocompatible and nontoxic poly(ethylene glycol) surface modification (PEGylation) can enhance NLC stability, although this may impair drug delivery and NLC clearance. To attain RIPL-NLC steric stabilization without impairing function, pH-sensitive cleavable PEG (cPEG) was grafted on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The idea is that the larger sized complex firstly achieves blood concentrations sufficient for its extravasation in the tumor, where the stimuli-sensitive release of smaller active agents occurs, which penetrate deeper into the tumor [38]. A similar approach has shown prospects for ovarian cancer treatment [39]. Another concept tested on ovarian carcinoma is to use cell-penetrating/tumor-targeting peptides for a better agent penetration into tumor/tumor cells [40,41], as well as cell-mediated delivery [34].…”
Section: Discussionmentioning
confidence: 99%
“…The idea is that the larger sized complex firstly achieves blood concentrations sufficient for its extravasation in the tumor, where the stimuli-sensitive release of smaller active agents occurs, which penetrate deeper into the tumor [38]. A similar approach has shown prospects for ovarian cancer treatment [39]. Another concept tested on ovarian carcinoma is to use cell-penetrating/tumor-targeting peptides for a better agent penetration into tumor/tumor cells [40,41], as well as cell-mediated delivery [34].…”
Section: Discussionmentioning
confidence: 99%
“…55,56 Thus, mPEG-C 2 -lipid is able to resist complete hydrolysis under physiological pH during at least 7 h. As compared to other pH-sensitive linkages used for endosomal escape technologies, our hemiacetal compound shows higher hydrolytic stability at physiological pH than a reported PEG-acetal-lipid (70% hydrolysis after 2 h) 57 and a PEG-hydrazone-lipid (80% hydrolysis after 2 h). 58…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that DNA-NLCs/TMZ improved anti-tumor potential and gene transfection efficacy by transferring the two of the drugs and gene into the gliomatosis cerebri [ 97 ]. To tackle this issue, Kim et al [ 98 ] designed RIPL peptide NLCs conjugated with cleavable PEG that was released from the nanocarrier surface at the tumor position in an acidic environment. The hydrophobic anchor 1,2-dipalmitoyl-sn-glycero-3-phosphothioethanol (DPPE) was used to establish cleavable PEG, which was connected to the PEG3000 chain through a hydrazone bond [ 99 ].…”
Section: The Different Nanomedicines Designed For Brain Cancer Therapymentioning
confidence: 99%